Reducing Poverty and Investing in People : The New Role of Safety Nets in Africa - Monchuk, Victoria (Washington, DC: World Bank, 2013)
For two decades, Africa’s strong economic growth has paved the way for poverty reduction. Nevertheless, high chronic poverty levels persist, and the gap between income groups in terms of human capital and access to basic services is growing. Also, poor households are vulnerable to frequent shocks. By providing regular, reliable support to poor households and helping them invest in productive activities, targeted interventions such as safety nets help reduce persistent poverty, reverse the trend of increasing inequality, and build household resilience. Until recently, safety nets were implemented only on an ad hoc basis in Africa. However, in the wake of the global economic crisis, policy makers are increasingly viewing safety nets as core instruments for reducing poverty and managing risk. Also a momentum toward rationalizing public spending to provide more adequate and targeted support to the poorest is emerging in response to growing evidence that safety nets can successfully reduce poverty and vulnerability and promote inclusive growth. This book assesses the status and analyzes the objectives, features, systems, performance, and financing of safety nets in 22 African countries. It then identifies how governments and donors can strengthen safety net systems and protect and promote poor and vulnerable people. Overall, the book finds that safety nets are on the rise in Africa and are beginning to evolve from fragmented stand-alone programs into integrated systems. Social protection programming has started to change from largely emergency food aid programs to regular, predictable safety nets including targeted cash transfers and cash-for-work programs. Some countries, including Ghana, Kenya, Rwanda, and Tanzania, are working toward consolidating their programs into a national system. Impact evaluations of safety nets in Africa are also increasingly being undertaken and, with recent research into the productive aspects of cash transfer programs, have yielded encouraging evidence that safety nets reduce poverty and vulnerability. The timely analysis of safety nets in Africa provides a solid foundation for evidence-based policy dialogue and programming. As a result of the growing body of evidence that safety nets contribute to inclusive growth, African decision makers are now putting safety nets high on their development agendas.